FEATURES OF THE USE OF HEAT PUMPS IN THE HEATING SYSTEMS OF PRIVATE HOUSES - FINYK, Iryna (Herald of Khmelnytskyi National University. Technical sciences, 2022)
In the paper, it is investigated that economics is the main advantage of thermal pumps. The financial costs during the heating season are almost three times lower than natural gas. You do not need any permissions to connect. The operation of heat pump units is absolutely safe and environmentally friendly. Since ancient times, heat pump units have been used as alternative heating systems. Such systems are reliable, have a long term of operation and are the most environmentally friendly. Heat pump units are seen as a new step toward the development of more efficient and safer systems. The main heating of the house with the help of a heat pump unit has significant advantages over the operation of gas boilers. Energy-saving technologies for private building, slowly but confidently remove traditional types of heating. The only thing that keeps the widespread introduction of installations is the need for a significant initial investment of money. Most producers have long been working on cheaper technology, so the prospects of using heat pumps in the heat supply systems of private houses are rather optimistic. The number of sales is expected to increase by 10-15% soon. It has been established that in contrast to the boiler, the convector and other type of heater the heat pump unit does not produce heat. It transfers heat from one environment to another. For example, the heat pump installation of air-water is set for cooling of air outside of buildings and heating of water in boiler. This results in over 100% efficiency. The heat pump consumes electricity and generates heat. The ratio of these indicators characterizes its productivity. But the real efficiency of the heat pump can vary considerably. The lower the inlet temperature and the higher the outlet temperature, the lower the efficiency. According to expert estimates, it is possible to predict that more than 70% of thermal energy for heating systems and hot water supply in developed countries as of 2023 will be produced by heat pump units that use different types of low-potential heating sources.